GENDER STEREOTYPES PRESENTED IN POPULAR CHILDREN’S FAIRY TALES - PAWŁOWSKA, JOANNA (Society Register, 2021)
The article aims to contribute to the discussion on gender stereotypes in stories for children by mapping gender stereotypes in traditional fairy tales. The article presents fairy tales' value in children’s education and indicates potential dangers in traditional cultural transmissions, paying special attention to gender stereotypes. A selection of texts was analyzed in terms of their stereotypical gender portrayals. The methodological framework represents an interpretative paradigm in social sciences, using a qualitative method of analysis. The texts were purposely selected, and the most popular fairy tales were chosen: Cinderella, Snow White and Sleeping Beauty, which despite the passing of time, are still popular, widely read and also used in film adaptations. It was shown that in all analyzed fairy tales, there was a stereotypical division of roles according to gender. The article also presents possible ways to counteract gender stereotypes. A limitation of the article is that the analysis is limited to three fairy tales only, but the overarching value raises awareness of gender stereotypes in fairy tales for children.